INOVASI BPJS KESEHATAN DALAM PEMBERIAN LAYANAN KEPADA MASYARAKAT : APLIKASI MOBILE JKN - Ayu Wulanadary; Sudarman Sudarman; Ikhsan Ikhsan (Jurnal Public Policy, 2019)
This paper discusses service innovations carried out by BPJS Health through the JKN Mobile Application. Jkn mobile application is the latest innovation from BPJS Health in improving services to the community, especially in the field of health, but many people who have not used this application because many people do not know about this application. The purpose of this study is to assess the effectiveness of service innovations provided through the mobile application jkn. In this study, researchers used a qualitative research method with a descriptive approach to the determination of purposive sampling informant techniques. Measurement of effectiveness through three indicators namely: time factor, accuracy factor, and service delivery style factor. Based on the results of the study showed that the services and information provided through the application have been effective when viewed from the time needed to provide services, carefulness in service delivery and service delivery style that is not discriminatory because it is systemized with the mobile application.